Dynamics of Debt Behavior on Online Lending Application Users: Systematic Review - Hanan Muslim; Maftuhatul Muna; Syafira Ghina; Dian Veronika Sakti Kaloeti (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The increasingly life demands make people easy to do debt. One of the best way for people to get amount of money is through online lending application. This study aims to identify the dynamic of debt behavior on online lending application users through systematic literature review. Online database used in this study including Google Scholar, ScienceDirect, and SpringerLink. Based on review, we have found 30 articles that are compatible to this study. 5 of 30 articles are strongly selected to be reviewed. The criteria of these selected articles are International and National based research, full text is available and published from 2015-2022. Evaluation method PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) is used in this study. Result found that debt behavior on online lending application users caused by lower economic situation, social environment influence, and function factor of environment. A future study suggest to explore the negative impact of debt behavior experienced by lending application users.